Pengaruh Permainan Jigsaw Puzzle terhadap Kemampuan Pemecahan Masalah Anak Usia 5-6 Tahun di RA Ikhlasul Amal Medan - Fitria Nur Afni Siregar; Ahmad Syukri Sitorus (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study was to examine the effect of Jigsaw Puzzle games on the problem-solving abilities of children aged up to 6 years at Raudhatul Athfal Ikhlasul Amal Medan. This study involved 12 students from group B, using quantitative methodology and a pre-experimental one-group pretest-posttest design. Data were collected through observations using a rating scale instrument and statistically analyzed using the Shapiro-Wilk normality test and paired t-test using SPSS 26. The main findings indicated a significant effect on children's problem-solving abilities after the Jigsaw Puzzle game intervention. The low average pretest score increased in the posttest, supported by a very small t-test significance value (0.000), indicating a statistically significant difference. It was concluded that Jigsaw Puzzle games are an effective medium for stimulating early childhood problem-solving abilities, training logical thinking, spatial reasoning, patience, and motivation, and can be recommended for developing an Early Childhood Education curriculum.